Composite lithium supplementing material and preparation method and application thereof
By loading lithium carbonate in magnesium silicate mineral materials and using magnesium oxide catalysts, the catalyst deactivation problem is solved, the energy density and cycle life of the battery are improved, and the battery performance is improved.
Patent Information
- Application Number
- CN202411345734.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-14
AI Technical Summary
The catalyst in the existing composite lithium supplement materials is converted into an inactive component after deactivation, affecting battery performance and lacking effective solutions.
Magnesium silicate mineral materials are used as the matrix, and lithium supplementary materials such as lithium carbonate are loaded, and the charging potential is reduced through a magnesium oxide catalyst to form a synergistic effect, converting magnesium into magnesium carbonate to improve battery performance.
It significantly reduces the charging potential of lithium supplement material, improves the energy density, ionic conductivity, rate performance and cycle life of the battery, and enhances the structural stability and active specific surface area of the positive electrode material.
Smart Images

Figure CN119315033A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and in particular relates to a composite lithium supplement material and a preparation method and application thereof. Background Art
[0002] The rapid development of electric vehicles and electrochemical energy storage technology has put forward higher requirements for battery energy density, and the limitations of traditional lithium-ion batteries in energy density have become increasingly prominent. One of the keys to improving battery energy density is to improve the Coulombic efficiency of the anode, because compared with the cathode, the anode will experience significant lithium loss in the initial cycle, mainly due to the formation of the solid electrolyte interface (SEI) and the electroplating of metallic lithium. Therefore, the development of pre-lithiation technology to compensate for this loss of active lithium has become the focus of improving the energy density of the whole battery.
[0003] In pre-lithiation technology, materials based on anion oxidation mechanism, such as Li2S, Li3N, Li2O, Li5FeO4, Li6CoO4, Li2CO3, etc., have been widely studied. However, when lithium-supplementing materials such as Li2CO3 are used as positive electrode lithium-supplementing materials, the charging platform potential far exceeds the voltage upper limit of the actual battery system. In order to make these materials ideal positive electrode lithium-supplementing materials, their decomposition potential needs to be adjusted to a range compatible with the working voltage of industrial batteries.
[0004] At present, many types of catalysts have been developed to reduce the charging potential of lithium-supplementing materials such as lithium carbonate, such as various metal oxide catalysts. After the lithium-supplementing materials are compounded with these high-efficiency metal oxide catalysts, the charging platform potential of the lithium-supplementing materials in the battery can be close to that of the battery system. However, after the catalyst is deactivated, it not only occupies a small proportion as an ineffective component in the positive electrode material, but it may also react with the electrolyte due to the characteristics of the metal oxide. However, the prior art lacks an effective solution to the negative impact of the catalyst on the electrode material after deactivation. Therefore, how to solve the negative impact of the catalyst and further convert the deactivated catalyst into an additive that is beneficial to the battery system to positively strengthen the entire battery system is a technical problem that urgently needs to be solved. Summary of the invention
[0005] The purpose of the present application is to provide a composite lithium supplement material and a preparation method and application thereof, aiming to solve the problem that the catalyst in the existing composite lithium supplement material is deactivated and converted into ineffective components, thereby affecting the battery performance.
[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0007] In a first aspect, the present application provides a composite lithium supplement material, comprising a matrix containing a magnesium silicate mineral material, and a lithium supplement material loaded in the matrix; the magnesium silicate mineral material has pores that can accommodate the lithium supplement material.
[0008] In some possible implementations, the substrate further includes a conductive material.
[0009] In some possible implementations, the magnesium silicate mineral material contains magnesium oxide.
[0010] In some possible implementations, the magnesium silicate mineral material is in a fibrous form.
[0011] In some possible implementations, the lithium supplement material includes at least one of lithium carbonate, lithium oxalate, and lithium squarate.
[0012] In some possible implementations, in the composite lithium-supplementing material, the particle D50 of the loaded lithium-supplementing material is 50 nm to 800 nm.
[0013] In some possible implementations, the magnesium silicate mineral material includes at least one of nano-sepiolite, serpentine, brucite, and hydromagnesite.
[0014] In some possible implementations, in the magnesium silicate mineral material, the average fiber diameter is 100 nm to 200 nm, and the fiber length is 2 μm to 10 μm.
[0015] In some possible implementations, the conductive material includes at least one of carbon nanofibers, carbon nanotube conductive fibers, graphene / carbon nanotube composite conductive nanofibers, and polyaniline conductive nanofibers.
[0016] In some possible implementations, in the conductive nanofibers, an average fiber diameter is 1 nm to 5 nm, and a fiber length is 1 μm to 20 μm.
[0017] In some possible implementations, the conductive material is conductive nanofibers, which are interwoven with fibers in the magnesium silicate mineral material to form a three-dimensional network structure.
[0018] In some possible implementations, the conductive material includes at least one of carbon nanofibers, carbon nanotube conductive fibers, graphene / carbon nanotube composite conductive nanofibers, and polyaniline conductive nanofibers.
[0019] In some possible implementations, the magnesium oxide is disposed in contact with the lithium supplement material within the pores of the magnesium silicate mineral material.
[0020] In some possible implementations, the mass percentage of the magnesium oxide in the magnesium silicate mineral material is 40% to 60%.
[0021] In some possible implementations, in the matrix, the mass ratio of the magnesium silicate mineral material to the conductive nanofiber is 1:(1-4).
[0022] In some possible implementations, in the composite lithium-supplementing material, the mass percentage of the lithium-supplementing material is 70% to 80%.
[0023] In some possible implementations, in the composite lithium supplement material, the mass percentage of the magnesium silicate mineral material is 4% to 15%.
[0024] In some possible implementations, in the composite lithium-supplementing material, the mass percentage of the conductive material is 10% to 25%.
[0025] In some possible implementations, in the composite lithium supplement material, the mass percentage of magnesium oxide is 2% to 7.5%.
[0026] In a second aspect, the present application provides a method for preparing a composite lithium supplement material, comprising the following steps:
[0027] Preparing a substrate comprising a magnesium silicate mineral material; the magnesium silicate mineral material having pores therein;
[0028] The lithium supplement material is loaded into the pores of the magnesium silicate mineral material to obtain a composite lithium supplement material. In some possible implementations, the matrix also contains a conductive material, and the preparation of the matrix includes the steps of: dissolving the magnesium silicate mineral material, a conductive material precursor, and a dispersant in water to form a hydrogel, and then freeze-drying to form an aerogel; and sintering the aerogel under an inert atmosphere to obtain the matrix with a three-dimensional network structure.
[0029] In some possible implementations, loading the lithium-supplementing material into the pores of the magnesium silicate mineral material includes the steps of: immersing the substrate in a solution of the lithium-supplementing material, taking it out and immersing it in an anti-solvent for stripping and recrystallization, and drying to obtain the composite lithium-supplementing material loaded with the lithium-supplementing material.
[0030] In some possible implementations, the lithium supplement material includes at least one recrystallizable lithium-rich material selected from lithium carbonate, lithium oxalate, and lithium squarate.
[0031] In some possible implementations, the magnesium silicate mineral material includes at least one of nano-sepiolite, serpentine, brucite, and hydromagnesite.
[0032] In some possible implementations, the conductive material precursor includes at least one of bacterial cellulose, graphene oxide, polyacrylonitrile, and thermoplastic polyurethane.
[0033] In some possible implementations, in the hydrogel, the mass ratio of the magnesium silicate mineral material to the conductive material precursor is 1:(2-20).
[0034] In some possible implementations, the mass percentage of the dispersant in the hydrogel is 0.3% to 0.8%.
[0035] In some possible implementations, the dispersant includes at least one of polyvinylidene fluoride, polyvinyl pyrrolidone, polyethylene oxide, and polyvinyl alcohol.
[0036] In some possible implementations, the temperature condition for preparing the hydrogel is 50°C to 80°C.
[0037] In some possible implementations, the heating rate of the sintering treatment is 1° C. / min to 5° C. / min, the holding temperature is 600° C. to 800° C., and the duration is 4 h to 8 h.
[0038] In some possible implementations, the solution of the lithium supplementing material is a saturated solution.
[0039] In some possible implementations, the anti-solvent includes at least one of ethanol, acetone, and tetrahydrofuran.
[0040] In some possible implementations, the recrystallization step may be repeated multiple times.
[0041] In some possible implementations, the temperature condition of the drying process is 200°C to 300°C.
[0042] In a third aspect, the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; wherein the positive electrode sheet contains the above-mentioned composite lithium supplement material or the composite lithium supplement material prepared by the above-mentioned method.
[0043] In some possible implementations, in the positive electrode material layer of the positive electrode sheet, the mass percentage of the composite lithium supplementing material is 1% to 3%.
[0044] In some possible implementations, the positive electrode material system of the secondary battery is a lithium iron phosphate system, and as the secondary battery operates, the magnesium salt in the composite lithium supplement material is converted into magnesium carbonate.
[0045] The composite lithium supplement material provided in the first aspect of the present application has pores in the magnesium silicate mineral material of the matrix that can accommodate the lithium supplement material, and the lithium supplement material is uniformly loaded in the pores of the matrix. Among them, the magnesium silicate mineral material has a high specific surface area and a very strong gas adsorption capacity; on the one hand, the catalytic substance in the magnesium silicate mineral material is magnesium oxide, and there are lattice defects and abundant acid-base active sites on the surface of magnesium oxide, which can promote the progress of specific chemical reactions. The interfacial interaction between magnesium oxide and the metal oxide of the lithium supplement material can produce a synergistic effect, thereby forming a supported metal catalyst with a unique structure and properties. This synergistic effect helps to improve the activity and selectivity of the composite lithium supplement material. It can significantly reduce the charging potential of the lithium supplement material, so that the charging platform potential of the lithium supplement material approaches the voltage of the battery system, and improve the lithium supplement effect of the composite lithium supplement material on the secondary battery. On the other hand, after the lithium supplement material is completely catalytically decomposed, the generated CO2 can be adsorbed in the magnesium silicate mineral material, and the magnesium salt in the magnesium silicate mineral material is converted into magnesium carbonate; the silicate part still serves as the supporting structure of the composite material, ensuring the stability of the cross-linked network. Among them, magnesium carbonate has the advantages of high specific surface area, excellent chemical stability, good thermal stability, and the ability to improve compatibility with other materials. It can be used as an additive for battery positive electrode materials, which can not only improve the structural stability of positive electrode materials, inhibit phase change, and reduce the volume change of materials during charging and discharging; but also increase the active specific surface area of positive electrode materials and increase the contact area with the electrolyte, thereby improving the battery's energy density, ionic conductivity, rate performance, cycle life and other electrochemical properties.
[0046] The preparation method of the composite lithium supplement material provided in the second aspect of the present application is to use a magnesium silicate mineral material with pores as a matrix, and then load the lithium supplement material into the pore structure of the magnesium silicate mineral material to obtain a composite lithium supplement material. The preparation process is simple and suitable for industrial large-scale production and application. The prepared composite lithium supplement material, the magnesium silicate mineral material has a high specific surface area and a strong gas adsorption capacity, contains magnesium oxide that can be used as a catalyst to reduce the charging potential of the lithium supplement material, so that the charging platform potential of the lithium supplement material approaches the voltage of the battery system, and improve the lithium supplement effect of the composite lithium supplement material on the secondary battery; and it can be used as an adsorption carrier to absorb the CO2 generated by the lithium supplement agent after delithiation, and convert the magnesium salt in the magnesium silicate mineral material into magnesium carbonate, thereby improving the structural stability of the positive electrode material, inhibiting phase change, increasing the active specific surface area of the positive electrode material, and increasing the contact area with the electrolyte, thereby improving the battery energy density, ionic conductivity, rate performance, cycle life and other electrochemical properties.
[0047] In the secondary battery provided in the third aspect of the present application, the positive electrode sheet contains the above-mentioned composite lithium supplement material, which not only has a large specific surface area and high conductivity, but can also significantly improve the wettability and conductivity of the composite lithium supplement material in the electrolyte; and the magnesium silicate mineral material contains magnesium oxide that can be used as a catalyst to reduce the charging potential of the lithium supplement material, so that the charging platform potential of the lithium supplement material approaches the voltage of the battery system, and improves the lithium supplement effect of the composite lithium supplement material on the secondary battery; and contains magnesium salts that can be used as adsorption carriers to absorb the CO2 generated by the lithium supplement agent after delithiation and convert it into magnesium carbonate, thereby improving the structural stability of the positive electrode material, inhibiting phase change, and increasing the active specific surface area of the positive electrode material. Thereby, the contact area between the positive electrode sheet and the electrolyte is increased, and the electrochemical properties of the secondary battery, such as the energy density, ionic conductivity, rate performance, and cycle life, are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0049] Figure 1 This is a SEM image of the composite lithium supplement material provided in Example 1 of the present application;
[0050] Figure 2 It is a schematic diagram of the process of preparing the composite lithium supplement material provided in the embodiment of the present application. DETAILED DESCRIPTION
[0051] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0052] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0053] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0054] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0055] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0056] The weight of the relevant components mentioned in the embodiments of the present specification can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components in the embodiments of the present specification is proportionally enlarged or reduced, it is within the scope disclosed in the embodiments of the present specification. Specifically, the mass described in the embodiments of the present specification can be μg, mg, g, kg and other mass units known in the chemical industry.
[0057] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0058] In recent years, in order to improve the energy density of batteries, the development of pre-lithiation technology to compensate for the loss of active lithium has become the focus of improving the energy density of the whole battery. In the pre-lithiation technology, materials based on anion oxidation mechanism, such as Li2S, Li3N, Li2O, Li5FeO4, Li6CoO4, Li2CO3, etc., have been widely studied. Among them, Li2CO3 has become a research hotspot in the field of pre-lithiation due to its excellent air stability and unique gaseous decomposition characteristics. The theoretical specific capacity of Li2CO3 is as high as 724mAh·g -1 , and during the battery assembly process, its decomposition products can be effectively discharged without leaving any residue, which makes Li2CO3 show great potential in pre-lithiation applications. However, as a wide-bandgap insulator, direct electrochemical decomposition of Li2CO3 faces challenges. Its theoretical thermodynamic decomposition potential is 3.82V (vs Li / Li + ), but in experiments, the initial decomposition potential of Li2CO3 is usually higher than 4.0V (vs Li / Li + In batteries using pure Li2CO3 as the active material, the charging platform potential is as high as 4.75V (vs Li / Li + ), far exceeding the voltage limit of actual battery systems. In order to make Li2CO3 an ideal positive electrode lithium supplement material, its decomposition potential needs to be regulated to a range compatible with the operating voltage of industrial batteries.
[0059] At present, a variety of catalysts have been developed to reduce the charging potential of lithium carbonate and other lithium-supplementing materials, such as various metal oxide catalysts. These highly efficient catalysts have reduced the charging platform potential of batteries with pure Li2CO3 as the active material to nearly 4V (vs Li / Li + ). However, after the catalyst is deactivated, it not only occupies a small proportion as an ineffective component in the positive electrode material, but also may react with the electrolyte due to the characteristics of the metal oxide. However, there is no effective solution to the negative impact of catalyst deactivation on electrode materials in the known technology. Therefore, how to solve the negative impact of the catalyst and further convert the deactivated catalyst into an additive that is beneficial to the battery system and positively strengthen the entire battery system is a technical problem that needs to be solved urgently.
[0060] Based on this, a first aspect of an embodiment of the present application provides a composite lithium supplement material, including a matrix containing a magnesium silicate mineral material, and a lithium supplement material loaded in the matrix; the magnesium silicate mineral material has pores that can accommodate the lithium supplement material.
[0061] The composite lithium supplement material provided in the first aspect of the embodiment of the present application has pores that can accommodate the lithium supplement material in the magnesium silicate mineral material of the matrix, and the lithium supplement material is uniformly loaded in the pores of the matrix. Among them, the magnesium silicate mineral material has a high specific surface area and contains magnesium oxide, has a high catalytic property to the lithium supplement material, and has a very strong gas adsorption capacity, and can be used as an adsorption carrier. On the one hand, the catalytic substance in the magnesium silicate mineral material is magnesium oxide, and there are lattice defects and abundant acid-base active sites on the surface of magnesium oxide, which can promote the progress of specific chemical reactions. The interfacial interaction between magnesium oxide and the metal oxide of the lithium supplement material can produce a synergistic effect, thereby forming a loaded metal catalyst with a unique structure and properties. This synergistic effect helps to improve the activity and selectivity of the composite lithium supplement material. It can significantly reduce the charging potential of the lithium supplement material, make the charging platform potential of the lithium supplement material close to the voltage of the battery system, and improve the lithium supplement effect of the composite lithium supplement material on the secondary battery. On the other hand, after the lithium supplement material is completely catalytically decomposed, the generated CO2 can be adsorbed in the magnesium silicate mineral material, converting the magnesium salt in the magnesium silicate mineral material into magnesium carbonate (MgO+CO2→MgCO3; Mg(OH)2+CO2→MgCO3+H2O); the silicate part still serves as the supporting structure of the composite material, ensuring the stability of the cross-linked network. Among them, magnesium carbonate has the advantages of high specific surface area, excellent chemical stability, good thermal stability, and the ability to improve compatibility with other materials. It can be used as an additive for battery positive electrode materials, which can not only improve the structural stability of positive electrode materials, inhibit phase change, and reduce the volume change of materials during charging and discharging; but also increase the active specific surface area of positive electrode materials and increase the contact area with electrolyte, thereby improving the battery energy density, ionic conductivity, rate performance, cycle life and other electrochemical properties.
[0062] In some possible implementations, the lithium supplement material includes at least one of lithium carbonate, lithium oxalate, and lithium squarate. These lithium supplement materials have a good lithium supplement effect on the positive electrode materials in the battery, and can effectively compensate for the loss of active lithium during the battery's cyclic charge and discharge process. Among them, lithium carbonate has excellent air stability and unique gaseous decomposition characteristics, Li2CO3→Li2O+CO2. Lithium oxalate has a high specific energy, good cycle stability, and can provide a longer battery life. Lithium squarate Li2C4O4 is a very ideal positive electrode pre-lithiation agent. By adding it to the positive electrode sheet, it can achieve efficient lithium supplementation of the negative electrode materials of lithium-ion batteries and lithium metal batteries. This lithium supplementation effect can significantly improve the cycle life and capacity of the battery.
[0063] In some possible implementations, in the composite lithium supplement material, the particle D50 of the loaded lithium supplement material is 50nm to 800nm. Specifically, it can be 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, etc., typical but non-restrictive arbitrary point values or interval values between any two point values. In this case, the lithium supplement material with a small particle size can be more evenly distributed in the pore structure of the matrix. And the lithium supplement material with a small particle size can increase the specific surface area of the active material and reduce the diffusion path of lithium ions in the battery, thereby improving the electrochemical reactivity of the lithium ion battery and improving the material capacity utilization. This helps to improve the charge and discharge rate and efficiency of the battery. In addition, a smaller particle size helps to reduce the delithiation potential, making it closer to the potential range of the positive electrode material, thereby improving the overall performance of the battery.
[0064] In some possible implementations, magnesium silicate mineral materials contain magnesium oxide, and the surface of magnesium oxide has lattice defects and abundant acid-base active sites, which can promote specific chemical reactions, so magnesium oxide has a catalytic effect. The interfacial interaction between magnesium oxide and the metal oxide of the lithium supplement material can produce a synergistic effect, thereby forming a supported metal catalyst with unique structure and properties. This synergistic effect helps to improve the activity and selectivity of the composite lithium supplement material.
[0065] In some possible implementations, magnesium oxide is disposed in contact with the lithium supplementing material in the pores of the magnesium silicate mineral material, which is more conducive to the contact reaction between magnesium oxide and the lithium supplementing material.
[0066] In some possible implementations, the mass percentage of magnesium oxide in the magnesium silicate mineral material is 40% to 60%, and can be any typical but non-restrictive point value such as 40%, 50%, 60%, or an interval value between any two points. In this case, the content of magnesium oxide fully ensures the improvement of the activity and selectivity of the composite lithium supplement material.
[0067] In some possible implementation methods, taking sepiolite nanofibers as an example, its magnesium oxide content accounts for 50%, which can efficiently catalyze lithium carbonate. The magnesium oxide catalyst in the magnesium silicate mineral material has played a role before the battery capacity is divided. The magnesium oxide in the magnesium silicate mineral material plays a catalytic effect, greatly reducing the lithium delithiation potential of lithium carbonate, so that it releases its capacity before the cut-off potential of 4.2V. After that, the magnesium oxide loses its activity and becomes an invalid component. It relies on the catalytic mineral itself to absorb the CO2 gas produced by the decomposition of lithium carbonate, and slowly converts into magnesium carbonate in the subsequent cycle process. Magnesium carbonate can not only improve the structural stability of the positive electrode material, inhibit phase change, and reduce the volume change of the material during the charge and discharge process. It can also increase the active specific surface area of the positive electrode material and increase the contact area with the electrolyte, thereby improving the battery energy density, ionic conductivity, rate performance, cycle life and other electrochemical properties.
[0068] In some possible implementations, the magnesium silicate mineral material is in fibrous form; it has a higher specific surface area, which is also beneficial for improving the gas adsorption capacity, and the pores in the three-dimensional network structure formed by the interlacing of the fibers can accommodate lithium supplement materials.
[0069] In some possible implementations, the magnesium silicate mineral material includes at least one of nano-sepiolite, serpentine, brucite, and hydromagnesite. These minerals all contain magnesium silicate fibers, which can not only catalytically reduce the charge and discharge voltage platform of the lithium supplement material, but also help improve the performance of the battery such as capacity and energy density. In particular, nano-sepiolite has a tubular through-channel with a cross-sectional area of 0.36nm×1.06nm and a diameter of up to 900m 2 / g of theoretical surface area, so it has water channels and pores as well as a large surface area. A large amount of water or polar substances, including low-polar substances, can be adsorbed in the channels and pores, so sepiolite has a strong adsorption capacity. Strong adsorption and a large specific surface area that can be treated and improved make it a good catalyst carrier. In addition, some surface properties of sepiolite (such as weak surface acidity, magnesium ions are easily replaced by other ions, etc.) make it itself a catalyst for certain reactions. Therefore, sepiolite is not only a good adsorbent, but also a good catalyst and catalyst carrier. The crystal structure of sepiolite has a continuous silicon-oxygen tetrahedral layer. At the same time, it has the characteristics of high resistance, strong adsorption (absorbing water greater than 150% of its own weight), strong water absorption rate (160%~200%), saturated brine adsorption rate (180%~260%), high thermal stability (1300℃ loses moisture and retains water, zeolite water; 200~600℃ loses crystallization water, and the structure does not change much; 600~700℃ loses structural water; 820℃ generates a new phase - enstatite), phase transition (20~80MPa, 22~76 hours; above 500 degrees, below 600℃ is a mixture of montmorillonite and chlorite), suspension (sepiolite is easily dispersed in water or other strong and medium polar solvents to form a network, and is almost unaffected by electrolytes) and so on.
[0070] In some possible implementations, the magnesium silicate mineral material is fibrous, and in the magnesium silicate mineral material, the average fiber diameter is 100nm to 200nm, and the fiber length is 2μm to 10μm. In this case, the magnesium silicate mineral material has a small diameter and a long length, which not only increases the active specific surface area of the magnesium silicate mineral material, but also facilitates the magnesium silicate mineral material and the conductive nanofibers to interweave to form a three-dimensional network structure. Exemplarily, in the magnesium silicate mineral material, the average fiber diameter can be 100nm, 120nm, 140nm, 150nm, 160nm, 180nm, 200nm, etc., typical but non-restrictive arbitrary point values or interval values between any two point values, and the fiber length can be 2μm, 4μm, 6μm, 8μm, 10μm, etc., typical but non-restrictive arbitrary point values or interval values between any two point values.
[0071] In some possible implementations, the matrix also includes a conductive material to improve the electrical conductivity of the composite lithium supplement material.
[0072] In some possible implementations, such as the attached Figure 1As shown, the conductive material is conductive nanofibers, which are interwoven with the fibers in the magnesium silicate mineral material to form a three-dimensional network structure. In this case, the lithium supplement material is uniformly loaded in the three-dimensional network structure of the matrix having the magnesium silicate mineral material and the conductive nanofibers interwoven, and the large specific surface area and high conductivity of the conductive nanofibers therein can significantly improve the wettability and conductivity of the composite lithium supplement material in the electrolyte.
[0073] In some possible implementations, the conductive material includes at least one of carbon nanofibers, carbon nanotube conductive fibers, graphene / carbon nanotube composite conductive nanofibers, and polyaniline conductive nanofibers. These fiber materials have large specific surface areas and high conductivity, and can significantly improve the wettability and conductivity of the composite lithium supplement material in the electrolyte.
[0074] In some possible implementations, in the conductive nanofibers, the average fiber diameter is 1nm to 5nm, and the fiber length is 1μm to 20μm. In this case, the conductive nanofibers have a small diameter, a long length, and a large active specific surface area, which is also conducive to the interweaving of magnesium silicate mineral materials and conductive nanofibers to form a three-dimensional network structure. Exemplarily, in the conductive nanofibers, the average fiber diameter can be 1nm, 2nm, 3nm, 4nm, 5nm, etc., typical but non-restrictive arbitrary point values or interval values between any two point values, and the fiber length is 1μm, 5μm, 10μm, 15μm, 20μm, etc., typical but non-restrictive arbitrary point values or interval values between any two point values.
[0075] In some possible implementations, the mass ratio of the magnesium silicate mineral material and the conductive nanofiber in the matrix is 1:(1-4). In this case, the ratio of the magnesium silicate mineral material and the conductive nanofiber is conducive to forming a stable three-dimensional network structure, and fully ensures the catalytic performance and conductive performance of the composite lithium supplement material, and comprehensively improves the electrochemical performance of the positive electrode material. Exemplarily, in the matrix, the mass ratio of the magnesium silicate mineral material and the conductive nanofiber can be 1:1, 1:2, 1:3, 1:4, etc., typical but non-restrictive arbitrary point values or interval values between any two point values.
[0076] In some possible implementations, the mass percentage of magnesium silicate mineral material in the composite lithium supplement material is 4% to 15%; specifically, it can be 4%, 5%, 8%, 10%, 12%, 14%, 15% and other typical but non-restrictive arbitrary point values or interval values between any two point values. In this case, the catalytic performance and conductive performance of the composite lithium supplement material are fully ensured, and the electrochemical performance of the positive electrode material is comprehensively improved.
[0077] In some possible implementations, the mass percentage of magnesium oxide in the composite lithium supplement material is 2% to 7.5%, and can be any typical but non-restrictive point value such as 2%, 4%, 5%, 6%, 7%, 7.5%, or an interval value between any two points. In this case, the catalytic performance of the composite lithium supplement material is fully ensured.
[0078] In some possible implementations, the mass percentage of the conductive material in the composite lithium supplement material is 10% to 25%; specifically, it can be any typical but non-restrictive point value such as 10%, 15%, 20%, 25%, 30%, or an interval value between any two points. In this case, the wettability and conductivity of the composite lithium supplement material in the electrolyte can be significantly improved.
[0079] In some possible implementations, the mass percentage of the lithium supplement material in the composite lithium supplement material is 70% to 80%. In this case, the content of the lithium supplement material fully ensures the lithium supplement effect of the composite lithium supplement material on the positive electrode material, ensures the effective supplement of the lithium ions lost during the battery charge and discharge cycle, and improves the cycle life of the battery.
[0080] The composite lithium supplement material provided in the present application can be prepared by the following example method.
[0081] The second aspect of the present application provides a method for preparing a composite lithium supplement material, as shown in the attached Figure 2 As shown, the following steps are included:
[0082] S10. Preparing a matrix comprising a magnesium silicate mineral material; the magnesium silicate mineral material having pores;
[0083] S20. Loading the lithium supplement material into the pores of the magnesium silicate mineral material to obtain a composite lithium supplement material.
[0084] The preparation method of the composite lithium supplement material of the embodiment of the present application uses a magnesium silicate mineral material with pores as a matrix, and then loads the lithium supplement material into the pore structure of the magnesium silicate mineral material to obtain a composite lithium supplement material. The preparation process is simple and suitable for industrial large-scale production and application. The prepared composite lithium supplement material, the magnesium silicate mineral material has a high specific surface area and a strong gas adsorption capacity, contains magnesium oxide that can be used as a catalyst to reduce the charging potential of the lithium supplement material, so that the charging platform potential of the lithium supplement material approaches the voltage of the battery system, and improves the lithium supplement effect of the composite lithium supplement material on the secondary battery; and it can be used as an adsorption carrier to absorb the CO2 generated by the lithium supplement agent after delithiation, and convert the magnesium salt in the magnesium silicate mineral material into magnesium carbonate, thereby improving the structural stability of the positive electrode material, inhibiting phase change, increasing the active specific surface area of the positive electrode material, and increasing the contact area with the electrolyte, thereby improving the battery energy density, ionic conductivity, rate performance, cycle life and other electrochemical properties.
[0085] In the above step S10:
[0086] In some possible implementations, the magnesium silicate mineral material is in fibrous form; it has a higher specific surface area, which is also beneficial for improving the gas adsorption capacity, and the pores in the three-dimensional network structure formed by the interlacing of the fibers can accommodate lithium supplement materials.
[0087] In some possible implementations, the matrix also contains a conductive material, and the preparation of the matrix includes the steps of: dissolving the magnesium silicate mineral material, the conductive material precursor, and the dispersant in water to form a hydrogel, and then freeze-drying to form an aerogel; sintering the aerogel under an inert atmosphere to obtain a matrix with a three-dimensional network structure. In this case, the magnesium silicate mineral material and the conductive material precursor are first made into a hydrogel, wherein the dispersant is used to improve the dispersion performance of the components, and then the hydrogel is filtered to remove excess solvent and freeze-dried to remove the internal solvent of the hydrogel, while maintaining the three-dimensional network structure of the gel to obtain an aerogel. The conductive material precursor is then converted into conductive nanofibers through sintering, and impurities such as solvents and dispersants in the aerogel are removed. A matrix with a three-dimensional network structure interwoven with conductive nanofibers and magnesium silicate mineral materials is obtained. Relying on the large specific surface area and high conductivity of the conductive nanofibers, the wetting performance and conductivity of the composite lithium supplement material in the electrolyte can be significantly improved.
[0088] In some possible implementations, the lithium supplement material includes at least one of lithium carbonate, lithium oxalate, and lithium quarate, which are recrystallizable lithium-rich materials. On the one hand, these lithium supplement materials have a good lithium supplement effect on the positive electrode materials in the battery, and can effectively compensate for the loss of active lithium during the battery's cyclic charge and discharge process. On the other hand, these lithium supplement materials are all recrystallizable lithium-rich materials, which can be uniformly loaded into the three-dimensional network structure of the matrix by recrystallization.
[0089] In some possible implementations, the magnesium silicate mineral material includes at least one of nano-sepiolite, serpentine, brucite, and hydromagnesite; these minerals all contain magnesium silicate fibers, which can not only catalytically reduce the charge and discharge voltage platform of the lithium supplement material, but also help to improve the battery's capacity, energy density and other performance.
[0090] In some possible implementations, the conductive material precursor includes at least one of bacterial cellulose, graphene oxide, polyacrylonitrile, and thermoplastic polyurethane. Among them, bacterial cellulose exists as a carbon nanofiber precursor, and bacterial cellulose itself can cross-link with each other to form a hydrogel, which can construct a three-dimensional conductive network space, which is conducive to reducing the voltage potential of the lithium supplement material.
[0091] In some possible implementations, in the hydrogel, the mass ratio of the magnesium silicate mineral material to the conductive material precursor is 1: (2 to 20). In this case, the ratio of the magnesium silicate mineral material to the conductive material precursor is not only conducive to the formation of a stable three-dimensional network structure, but also fully ensures the catalytic performance and conductive performance of the composite lithium supplement material, and comprehensively improves the electrochemical performance of the positive electrode material. And, in this case, the mass ratio of the magnesium silicate mineral material and the conductive nanofiber in the prepared matrix can be maintained between 1: (1 to 4). Exemplarily, in the hydrogel, the mass ratio of the magnesium silicate mineral material to the conductive material precursor can be 1:2, 1:4, 1:5, 1:6, 1:8, 1:10, 1:12, 1:14, 1:16, 1:18, 1:20, etc., typical but non-restrictive arbitrary point values or interval values between any two point values.
[0092] In some possible implementations, the mass percentage of the dispersant in the hydrogel is 0.3% to 0.8%. In this case, the dispersion stability of the magnesium silicate mineral material and the conductive material precursor can be fully ensured, which is conducive to the cross-linking of the two to form a stable three-dimensional network conductive structure. Exemplarily, in the hydrogel, the mass percentage of the dispersant can be 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, etc., typical but non-restrictive arbitrary point values or interval values between any two point values.
[0093] In some possible implementations, the dispersant includes at least one of polyvinylidene fluoride PVDF, polyvinyl pyrrolidone PVP, polyethylene oxide PEO, and polyvinyl alcohol PVA. These dispersants are long-chain hydroxyl-rich polymers that can better promote the dispersion of magnesium silicate mineral materials and conductive material precursors in the solution.
[0094] In some possible implementations, the temperature condition for preparing the hydrogel is 50°C to 80°C. In this case, the magnesium silicate mineral material, the conductive material precursor, and the dispersant are dissolved in water, and the hydroxyl groups and hydrogen bonds in the components are cross-linked to form a hydrogel. Within this temperature range, the amount of water evaporation and the degree of cross-linking can be well controlled, and the reaction can be stopped in time. Exemplarily, the temperature condition for preparing the hydrogel can be any typical but non-restrictive point value such as 50°C, 60°C, 70°C, 80°C, or an interval value between any two point values.
[0095] In some possible implementations, the heating rate of the sintering process is 1°C / min to 5°C / min, the holding temperature is 600°C to 800°C, and the duration is 4h to 8h. In this case, the structure of the magnesium silicate mineral material is stable during the sintering process, and the structure and properties of the magnesium silicate mineral material will not be destroyed. Only dehydration reaction will occur; at the same time, the conductive material precursor can be converted into conductive nanofibers such as carbon nanofibers to remove excess impurity components. In some embodiments, after the sintering process, the mass loss of the magnesium silicate mineral material is less than 20%; and the residual mass of the conductive material precursor is about 20%. Exemplarily, the heating rate of the sintering treatment can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, etc., typical but non-limiting arbitrary point values, or an interval value between any two point values; the holding temperature can be 600°C, 650°C, 700°C, 750°C, 800°C, etc., typical but non-limiting arbitrary point values, or an interval value between any two point values; the duration can be 4h, 5h, 6h, 7h, 8h, etc., typical but non-limiting arbitrary point values, or an interval value between any two point values.
[0096] In the above step S20:
[0097] In some possible implementations, loading the lithium supplement material into the pores of the magnesium silicate mineral material includes the steps of: immersing the substrate in a solution of the lithium supplement material, taking it out and immersing it in an anti-solvent for stripping and recrystallization, and drying to obtain a composite lithium supplement material loaded with the lithium supplement material. In the embodiment of the present application, the anti-solvent stripping method is used to make the recrystallized lithium supplement material uniformly loaded into the three-dimensional network structure of the substrate, carrying lithium carbonate to form a composite lithium supplement material. In the embodiment of the present application, the magnesium silicate mineral material and the conductive nanofibers are cross-linked to form a three-dimensional space network, and the lithium supplement material is dissolved in an aqueous solution and adsorbed by the mineral cavity. A part of it relies on the mineral fiber for recrystallization, and a part of it is recrystallized in the three-dimensional space gap to form a composite lithium supplement material.
[0098] In some possible implementations, the solution of the lithium supplement material is a saturated solution. In this case, it is more conducive to fully adsorbing the lithium supplement material into the three-dimensional network structure of the matrix, which is conducive to increasing the loading amount.
[0099] In some possible implementations, the anti-solvent includes at least one of ethanol, acetone, and tetrahydrofuran. These anti-solvents can effectively extract the lithium supplement material, recrystallize the lithium supplement material, and uniformly and stably load it into the three-dimensional network structure of the matrix. In some embodiments, ethanol uses high-purity ethanol with a concentration of more than 99% to improve the recrystallization effect.
[0100] In some possible implementations, the recrystallization process can be repeated multiple times. In this case, the substrate is immersed in a solution of the lithium supplementing material, taken out and immersed in an anti-solvent for stripping and recrystallization, and the lithium supplementing material solution immersion and anti-solvent immersion are repeated multiple times in order to increase the loading amount of the lithium supplementing material in the three-dimensional network structure of the substrate.
[0101] In some possible implementations, the temperature condition of the drying treatment is 200°C to 300°C. Under this temperature condition, the solvent can be removed and the effect of high-temperature drying on the composite lithium supplement material can be reduced. Exemplarily, the temperature condition of the drying treatment can be 200°C, 230°C, 250°C, 280°C, 300°C, or any typical but non-limiting point value or an interval value between any two point values.
[0102] In a third aspect, an embodiment of the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; wherein the positive electrode sheet contains the above composite lithium supplement material or the composite lithium supplement material prepared by the above method.
[0103] In the secondary battery of the embodiment of the present application, the positive electrode sheet contains the above-mentioned composite lithium supplement material, which not only has a large specific surface area and high conductivity, but can significantly improve the wettability and conductivity of the composite lithium supplement material in the electrolyte; and the magnesium silicate mineral material contains magnesium oxide, which has catalytic properties, reduces the charging potential of the lithium supplement material, makes the charging platform potential of the lithium supplement material approach the voltage of the battery system, and improves the lithium supplement effect of the composite lithium supplement material on the secondary battery; and contains magnesium salts that can be used as adsorption carriers to absorb the CO2 generated by the lithium supplement agent after delithiation and convert it into magnesium carbonate, improve the structural stability of the positive electrode material, inhibit phase change, and increase the active specific surface area of the positive electrode material. Thereby, the contact area between the positive electrode sheet and the electrolyte is increased, and the electrochemical properties of the secondary battery, such as the energy density, ionic conductivity, rate performance, and cycle life, are improved.
[0104] The present application does not specifically limit the positive electrode sheet, negative electrode sheet, electrolyte, separator, etc. in the embodiment secondary battery, and can be applied to any battery system.
[0105] In some possible implementations, the positive electrode sheet includes a current collector and a positive electrode material layer formed on the surface of the current collector, and the positive electrode material layer includes the above-mentioned composite lithium supplement material or the composite lithium supplement material prepared by the above-mentioned method. The composite lithium supplement material has the characteristics of good structural stability, excellent lithium supplement effect, high conductivity, good rate performance, good cycle stability, etc., thereby improving the electrochemical properties of the positive electrode sheet, such as stability, capacity, rate performance, cycle performance, etc.
[0106] In some possible implementations, the positive electrode material system of the secondary battery is a lithium iron phosphate system. As the secondary battery operates, the magnesium salt in the composite lithium supplement material is converted into magnesium carbonate. In this case, the composite lithium supplement material added to the secondary battery adopts a three-dimensional spatial network structure constructed by magnesium-rich magnesium silicate minerals and carbon nanofibers. This structure can effectively adsorb the dissolved lithium supplement material and promote recrystallization in the mineral cavity and gap to form a composite lithium supplement material with excellent lithium supplement performance. The catalytic substance in the magnesium silicate mineral material is magnesium oxide. There are lattice defects and abundant acid-base active sites on the surface of magnesium oxide, which can promote the progress of specific chemical reactions. The interfacial interaction between magnesium oxide and the metal oxide of the lithium supplement material can produce a synergistic effect, thereby forming a supported metal catalyst with unique structure and properties. This synergistic effect helps to improve the activity and selectivity of the composite lithium supplement material. It can significantly reduce the charging potential of the lithium supplement material, make the charging platform potential of the lithium supplement material close to the voltage of the battery system, and improve the lithium supplement effect of the composite lithium supplement material on the secondary battery. In addition, after the lithium supplement material is completely catalytically decomposed, the generated CO2 can be adsorbed in the magnesium silicate mineral material, converting the magnesium salt in the magnesium silicate mineral material into magnesium carbonate; the silicate part still serves as the supporting structure of the composite material, ensuring the stability of the cross-linked network. Among them, magnesium carbonate has the advantages of high specific surface area, excellent chemical stability, good thermal stability, and the ability to improve compatibility with other materials. It can be used as an additive for battery positive electrode materials, which can not only improve the structural stability of the positive electrode material, inhibit phase change, and reduce the volume change of the material during charging and discharging; but also increase the active specific surface area of the positive electrode material and increase the contact area with the electrolyte, thereby improving the battery energy density, ionic conductivity, rate performance, cycle life and other electrochemical properties. It is of great significance to optimize the lithium supplement technology of lithium iron phosphate batteries and improve battery performance. By precisely controlling the composition and structure of the composite lithium supplement material, the long-term stability of the capacity of the secondary battery and the significant improvement of the cycle life can be achieved.
[0107] In some possible implementations, the mass percentage of the composite lithium supplement material in the positive electrode material layer of the positive electrode sheet is 1% to 3%, which can be any typical but non-restrictive point value such as 1%, 2%, 3%, or an interval value between any two point values. In this case, the amount of the composite lithium supplement material added to the material layer of the positive electrode sheet fully ensures the lithium supplement effect on the positive electrode sheet, can effectively supplement the loss of lithium ions during the charging and discharging process, and is also beneficial to improving the energy density, rate performance, cycle life and other performance of the battery.
[0108] In some possible implementations, the preparation of the positive electrode material layer includes the steps of: mixing the above-mentioned composite lithium supplement material, conductive agent and binder to form an electrode slurry, coating the electrode slurry on the current collector, and preparing a positive electrode sheet through steps such as drying, rolling and die cutting.
[0109] In some possible implementations, the current collector of the positive electrode sheet includes but is not limited to any one of copper foil and aluminum foil.
[0110] In some possible implementations, the content of the binder in the active material layer of the positive electrode sheet is 2 wt% to 5 wt%. In specific embodiments, the content of the binder can be 2 wt%, 3 wt%, 4 wt%, 5 wt%, etc., which are typical but not limiting contents.
[0111] In some possible implementations, the binder includes one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan, and chitosan derivatives.
[0112] In some possible implementations, the content of the conductive agent in the active material layer of the positive electrode sheet is 1 wt% to 5 wt%. In specific embodiments, the content of the conductive agent can be 3 wt%, 4 wt%, 5 wt%, etc., which are typical but not limiting contents.
[0113] In some possible implementations, the conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60, and carbon nanotubes.
[0114] In some possible implementations, the negative electrode active material of the secondary battery includes, but is not limited to, carbon materials such as graphite, soft carbon (such as coke), hard carbon, or nitrides, tin-based oxides, tin-based oxides, tin alloys, and nano-negative electrode materials, etc. The current collector includes, but is not limited to, any one of copper foil and aluminum foil.
[0115] In some possible embodiments, the steps of making a negative electrode sheet include: mixing a negative electrode active material with a conductive agent such as conductive carbon black, a binder such as carboxymethyl cellulose and styrene-butadiene rubber, and a solvent such as water in a mass ratio of (80-99):(1-5):(2-10):100 to make a negative electrode mixed slurry, vacuum degassing, discharging, coating on a coating machine, and obtaining a negative electrode sheet after rolling, slitting, and die-cutting.
[0116] In some possible implementations, the separator can block the passage of electrons and allow the passage of ions. Exemplarily, the separator includes, but is not limited to, at least one material selected from polypropylene fiber, polyacrylonitrile fiber, polyvinyl formal fiber, poly(ethylene terephthalate), polyethylene terephthalate, polyamide fiber, and poly(p-phenylene terephthalamide).
[0117] In some possible implementations, the electrolyte includes at least one soluble metal salt. In some specific embodiments, the metal salt includes LiClO4, LiBF4, LiPF6, LiAsF6, LiCF3SO3, LiTDI, Li[(CF3SO2)2N], Li[(FSO2)2N], Li[(C m F 2m+1 SO2)(C n F 2n+1 SO2)N], wherein m and n are natural numbers. These electrolytic salts can ensure high ionic conductivity of the electrolyte, and do not cause harmful side reactions with electrode materials, electrolytes, diaphragms, etc., and have good chemical stability.
[0118] In some possible implementations, the secondary battery includes at least one of a battery cell, a battery module, and a battery pack.
[0119] In some possible implementations, the battery cell types include lithium-ion batteries, as well as new batteries such as lithium-air batteries and lithium metal batteries.
[0120] In some possible implementations, the battery cells of the present application can be assembled into a battery module, and the number of battery cells contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module. Further, the battery module can also include a housing with a storage space, and multiple battery cells are stored in the storage space.
[0121] In a possible implementation, the battery cells and / or battery modules may also be assembled into a battery pack, and the number of battery cells or battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0122] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, and to demonstrate the significant performance improvements of the composite lithium supplement material and its preparation method and application in the embodiments of the present application, the above technical solution is illustrated by multiple embodiments below.
[0123] Example 1
[0124] A composite lithium supplement material, wherein the mass ratio of lithium carbonate to nano-sea foam fiber and conductive carbon fiber is 76:12:12, and the magnesium oxide catalyst accounts for 6% of the total mass. The preparation thereof comprises the following steps:
[0125] 1. Disperse nano-sepiolite powder and bacterial cellulose in an aqueous solution at a ratio of 1:5, add 0.5% PVDF as a dispersant, filter, heat and stir at 60°C for 1 hour to form a hydrogel, and freeze-dry for 24 hours to form an aerogel. Transfer to an argon atmosphere tube furnace, heat to 700°C at a heating rate of 2°C / min, and sinter for 5 hours to obtain nano-sepiolite fiber cross-linked carbon nanofibers.
[0126] 2. Place the nano-sepiolite fiber cross-linked carbon nanofiber aerogel in a saturated lithium carbonate aqueous solution, vigorously stir the solution for 1 hour and let it stand for 2 hours, filter out the precipitate, place it in an ethanol solution and let it stand for 1 hour, filter out the precipitate, and dry it in an oven at 80°C. Repeatedly immerse in a saturated lithium carbonate aqueous solution and an ethanol solution for 3 times to increase the lithium carbonate content in the composite. Finally, remove the moisture at a high temperature of 250°C to obtain a composite lithium supplement material.
[0127] Example 2
[0128] A composite lithium supplement material, wherein the mass ratio of lithium carbonate to nano-sea foam fiber and conductive carbon fiber is 70:15:15, and the magnesium oxide catalyst accounts for 7.5% of the total mass. The preparation thereof comprises the following steps:
[0129] 1. Disperse nano-sepiolite powder and bacterial cellulose in an aqueous solution at a ratio of 1:5, add 0.5% PVDF as a dispersant, filter, heat and stir at 60°C for 1 hour to form a hydrogel, and freeze-dry for 24 hours to form an aerogel. Transfer to an argon atmosphere tube furnace, heat to 700°C at a heating rate of 2°C / min, and sinter for 5 hours to obtain nano-sepiolite fiber cross-linked carbon nanofibers.
[0130] 2. Place the nano-sepiolite fiber cross-linked carbon nanofiber aerogel in a saturated lithium carbonate aqueous solution, vigorously stir the solution for 1 hour and let it stand for 2 hours, filter out the precipitate, place it in an ethanol solution and let it stand for 1 hour, filter out the precipitate, and dry it in an oven at 80°C. Repeatedly immerse it in a saturated lithium carbonate aqueous solution and an ethanol solution once to increase the lithium carbonate content in the composite. Finally, remove the moisture at a high temperature of 250°C to obtain a composite lithium supplement material.
[0131] Example 3
[0132] A composite lithium supplement material, wherein the mass ratio of lithium carbonate to nano-sea foam fiber and conductive carbon fiber is 80:4:16, and the magnesium oxide catalyst accounts for 2% of the total mass. The preparation thereof comprises the following steps:
[0133] 1. Disperse nano-sepiolite powder and bacterial cellulose in an aqueous solution at a ratio of 1:20, add 0.5% PVDF as a dispersant, filter, heat and stir at 60°C for 1 hour to form a hydrogel, and freeze-dry for 24 hours to form an aerogel. Transfer to an argon atmosphere tube furnace, heat to 700°C at a heating rate of 2°C / min, and sinter for 5 hours to obtain nano-sepiolite fiber cross-linked carbon nanofibers.
[0134] 2. Place the nano-sepiolite fiber cross-linked carbon nanofiber aerogel in a saturated lithium carbonate aqueous solution, vigorously stir the solution for 1 hour and let it stand for 2 hours, filter out the precipitate, place it in an ethanol solution and let it stand for 1 hour, filter out the precipitate, and dry it in an oven at 80°C. Repeatedly immerse in a saturated lithium carbonate aqueous solution and an ethanol solution for 6 times to increase the lithium carbonate content in the composite. Finally, remove the moisture at a high temperature of 250°C to obtain a composite lithium supplement material.
[0135] Example 4
[0136] A composite lithium supplement material, wherein the mass ratio of lithium carbonate to nano-sea foam fiber and conductive carbon fiber is 70:5:25, and the magnesium oxide catalyst accounts for 2.5% of the total mass. The preparation thereof comprises the following steps:
[0137] 1. Disperse nano-sepiolite powder and bacterial cellulose in an aqueous solution at a ratio of 1:20, add 0.5% PVDF as a dispersant, filter, heat and stir at 60°C for 1 hour to form a hydrogel, and freeze-dry for 24 hours to form an aerogel. Transfer to an argon atmosphere tube furnace, heat to 700°C at a heating rate of 2°C / min, and sinter for 5 hours to obtain nano-sepiolite fiber cross-linked carbon nanofibers.
[0138] 2. Place the nano-sepiolite fiber cross-linked carbon nanofiber aerogel in a saturated lithium carbonate aqueous solution, vigorously stir the solution for 1 hour and let it stand for 2 hours, filter out the precipitate, place it in an ethanol solution and let it stand for 1 hour, filter out the precipitate, and dry it in an oven at 80°C. Repeatedly immerse it in a saturated lithium carbonate aqueous solution and an ethanol solution once to increase the lithium carbonate content in the composite. Finally, remove the moisture at a high temperature of 250°C to obtain a composite lithium supplement material.
[0139] Example 5
[0140] A composite lithium supplement material, wherein the mass ratio of lithium carbonate to nano-sea foam fiber and conductive carbon fiber is 80:10:10, and the magnesium oxide catalyst accounts for 5% of the total mass. The preparation thereof comprises the following steps:
[0141] 1. Disperse nano-sepiolite powder and bacterial cellulose in an aqueous solution at a ratio of 1:1, add 0.5% PVDF as a dispersant, filter, heat and stir at 60°C for 1 hour to form a hydrogel, and freeze-dry for 24 hours to form an aerogel. Transfer to an argon atmosphere tube furnace, heat to 700°C at a heating rate of 2°C / min, and sinter for 5 hours to obtain nano-sepiolite fiber cross-linked carbon nanofibers.
[0142] 2. Place the nano-sepiolite fiber cross-linked carbon nanofiber aerogel in a saturated lithium carbonate aqueous solution, vigorously stir the solution for 1 hour and let it stand for 2 hours, filter out the precipitate, place it in an ethanol solution and let it stand for 1 hour, filter out the precipitate, and dry it in an oven at 80°C. Repeatedly immerse in a saturated lithium carbonate aqueous solution and an ethanol solution for 6 times to increase the lithium carbonate content in the composite. Finally, remove the moisture at a high temperature of 250°C to obtain a composite lithium supplement material.
[0143] Example 6
[0144] A composite lithium supplement material, wherein the mass ratio of lithium carbonate, nano-sea foam fiber and conductive carbon (block) is 76:12:12, and the magnesium oxide catalyst accounts for 6% of the total mass. The preparation thereof comprises the following steps:
[0145] 1. Disperse nano-sepiolite powder and glucose in an aqueous solution at a ratio of 1:5, add an appropriate amount of 3% acetic acid as a glucose dissolving agent, filter, heat and stir at 60°C for 1 hour to form a hydrogel, and freeze-dry for 24 hours to form an aerogel. Transfer to an argon atmosphere tube furnace, heat to 700°C at a heating rate of 2°C / min, and sinter for 5 hours to obtain a nano-sepiolite fiber cross-linked carbon material aerogel.
[0146] 2. Place the nano-sepiolite fiber cross-linked carbon material aerogel in a saturated lithium carbonate aqueous solution, vigorously stir the solution for 1 hour and let it stand for 2 hours, filter out the precipitate, place it in an ethanol solution and let it stand for 1 hour, filter out the precipitate, and dry it in an oven at 80°C. Repeatedly immerse in a saturated lithium carbonate aqueous solution and an ethanol solution for 3 times to increase the lithium carbonate content in the composite. Finally, remove the moisture at a high temperature of 250°C to obtain a composite lithium supplement material.
[0147] Example 7
[0148] A composite lithium supplement material, wherein the mass ratio of lithium oxalate to nano-sea foam fiber and conductive carbon fiber is 76:12:12, and the magnesium oxide catalyst accounts for 6% of the total mass. The preparation thereof comprises the following steps:
[0149] 1. Disperse nano-sepiolite powder and bacterial cellulose in an aqueous solution at a ratio of 1:5, add 0.5% PVDF as a dispersant, filter, heat and stir at 60°C for 1 hour to form a hydrogel, and freeze-dry for 24 hours to form an aerogel. Transfer to an argon atmosphere tube furnace, heat to 700°C at a heating rate of 2°C / min, and sinter for 5 hours to obtain nano-sepiolite fiber cross-linked carbon nanofibers.
[0150] 2. Place the nano-sepiolite fiber cross-linked carbon nanofiber aerogel in a saturated lithium oxalate aqueous solution, vigorously stir the solution for 1 hour and let it stand for 2 hours, filter out the precipitate, place it in an ethanol solution and let it stand for 1 hour, filter out the precipitate, and dry it in an oven at 80°C. Repeatedly immerse in a saturated lithium oxalate aqueous solution and an ethanol solution for 3 times to increase the lithium oxalate content in the composite. Finally, remove the moisture at a high temperature of 250°C to obtain a composite lithium supplement material.
[0151] Example 8
[0152] A composite lithium supplement material, wherein the mass ratio of lithium carbonate to nano-sea foam fiber and conductive carbon fiber is 76:12:12, and the magnesium oxide catalyst accounts for 6% of the total mass. The preparation thereof comprises the following steps:
[0153] 1. Disperse nano-sepiolite powder and bacterial cellulose in an aqueous solution at a ratio of 1:5, add 0.5% PVDF as a dispersant, filter, heat and stir at 60°C for 1 hour to form a hydrogel, and freeze-dry for 24 hours to form an aerogel. Transfer to an argon atmosphere tube furnace, heat to 700°C at a heating rate of 2°C / min, and sinter for 5 hours to obtain nano-sepiolite fiber cross-linked carbon nanofibers.
[0154] 2. Mix lithium carbonate powder and aerogel at a mass ratio of 76:24 by high-speed ball milling for 24 hours to obtain a composite lithium supplement material.
[0155] Comparative Example 1
[0156] A composite lithium supplement material, wherein the mass ratio of lithium carbonate to magnesium oxide is 76:12. The preparation thereof comprises the following steps:
[0157] The lithium carbonate powder and the nano magnesium oxide powder were mixed by high-speed ball milling at a mass ratio of 76:12 for 24 hours to obtain a composite lithium supplement material.
[0158] Comparative Example 2
[0159] A composite lithium supplement material, wherein the mass ratio of lithium carbonate to magnesium carbonate is 76:12. The preparation thereof comprises the following steps:
[0160] The lithium carbonate powder and the nano magnesium carbonate powder were mixed by high-speed ball milling at a mass ratio of 76:12 for 24 hours to obtain a composite lithium supplement material.
[0161] The components and proportions of the composite lithium supplement materials of the above embodiments and comparative examples are shown in Table 1 below:
[0162] Table 1
[0163]
[0164]
[0165] In order to verify the progress of the embodiments of the present application, the following performance tests were performed on the above embodiments and comparative examples respectively:
[0166] 1. The morphology of the composite lithium supplement material prepared in Example 1 was observed, and the test results are shown in the attached Figure 1 As shown in the scanning electron microscope (SEM) image, it can be seen that the magnesium silicate mineral material and the conductive nanofibers form a matrix with a three-dimensional network structure, and the lithium supplement additive is evenly distributed in the three-dimensional network structure of the matrix.
[0167] 2. The composite lithium supplement materials provided in Examples 1 to 8 and Comparative Examples 1 to 2 were applied to the secondary battery for electrochemical performance testing, and a control group without adding the lithium supplement material was set up:
[0168] 2.1 Button battery assembly and performance test:
[0169] Positive electrode sheet: The composite lithium supplement material, SP and PVDF are mixed in a mass ratio of 90:4:6 to form a positive electrode slurry, the positive electrode slurry is coated on the surface of aluminum foil, vacuum dried at 110°C overnight, and rolled to obtain a positive electrode sheet;
[0170] Lithium-ion button cell assembly: Assemble button cells in an inert atmosphere glove box in the order of negative electrode sheet - separator - electrolyte - positive electrode sheet.
[0171] The electrochemical performance of each lithium ion button cell assembled in the above embodiment was tested under the following test conditions:
[0172] Rate charging test: Charge and discharge at a rate of 0.1C, with a charge cutoff voltage of 4.5V and a discharge cutoff voltage of 2.5V; observe the charging platform during the charging process to obtain the delithiation potential of the lithium supplement material.
[0173] 2.2 Soft pack battery assembly and performance testing:
[0174] The positive electrode sheet of the soft-pack battery is composed of active material LFP, composite lithium supplement material, SP and PVDF in a mass ratio of 96:2:1:1, added to an appropriate amount of NMP and mixed evenly.
[0175] Lithium-ion soft-pack battery assembly: The positive and negative electrodes are wound, injected, and the tabs are welded to form a soft-pack battery.
[0176] The lithium-ion soft-pack batteries assembled in the above embodiments were subjected to electrochemical performance tests under the following test conditions:
[0177] (1) Rate test: Charge and discharge at a rate of 0.1C, with a charge cut-off voltage of 4.2V and a discharge cut-off voltage of 2.5V to test the battery capacity performance and lithium replenishment capacity.
[0178] (2) Cycle life test: Charge and discharge at a 1C rate to test the number of cycles when the battery capacity decays to 80%.
[0179] The above test results are shown in Table 2 below:
[0180] Table 2
[0181]
[0182] The lithium replenishment capacity is calculated by the formula: lithium replenishment capacity = (first charge capacity - 166*94 / 96) / (2 / 96).
[0183] It can be seen from the control group that the first charge capacity of the standard lithium iron phosphate battery at 0.1C is 166mAh / g. After 925 charge and discharge cycles, the capacity drops below 80%. Comparative Example 1 The composite lithium supplement material is directly ball-milled and mixed by the lithium supplement material and the catalytic material. Since there is no carbon material to increase the conductivity, its lithium supplement effect is poor, and the lithium desorption platform is high. Comparative Example 2 is a lithium supplement material formed by a composite of lithium carbonate and lithium supplement material. There is no catalyst and conductive material. This material has no lithium supplement effect. The lithium supplement material accounts for 2% of the mass of the soft-pack positive electrode, which causes the first charge capacity and cycle life to decay.
[0184] The composite lithium supplement material provided in the embodiment of the present application includes magnesium-rich silicate minerals and carbon nanofibers cross-linked to form a three-dimensional space network. The lithium supplement material is dissolved in an aqueous solution and adsorbed by the mineral cavity. A part of it relies on the mineral fiber for recrystallization, and a part of it is recrystallized in the three-dimensional space gap to form a composite lithium supplement material. Taking sepiolite nanofibers as an example, its magnesium oxide content accounts for 50%, which can efficiently catalyze lithium carbonate. The catalyst has played a role before the battery capacity is divided. The magnesium oxide in the catalytic material plays a catalytic effect, greatly reducing the lithium desorption potential of lithium carbonate, so that it releases the capacity before the cut-off potential of 4.2V. After that, the magnesium oxide loses its activity and becomes an invalid component. It relies on the catalytic mineral itself to absorb the CO2 gas generated by the decomposition of lithium carbonate, and slowly converts into magnesium carbonate in the subsequent cycle process. Magnesium carbonate can not only improve the structural stability of the positive electrode material, inhibit phase change, and reduce the volume change of the material during charging and discharging; but also increase the active specific surface area of the positive electrode material, increase the contact area with the electrolyte, thereby improving the battery energy density, ionic conductivity, rate performance, cycle life and other electrochemical properties.
[0185] The results of Examples 1-5 show that by adjusting the ratio of catalytic materials and carbon materials, the lithium replenishment effect of the composite lithium replenishment material and the cycle life of the battery can be significantly improved. The ratio of catalytic materials and carbon materials needs to be balanced to ensure that the lithium carbonate in the three-dimensional space is fully catalyzed while maintaining good electrical conductivity. A reasonable ratio of magnesium silicate mineral materials and conductive carbon materials can enable the composite lithium replenishment material to exert excellent lithium replenishment performance and greatly improve the battery cycle life. When the proportion of catalytic materials is high, the catalytic effect is good, but the catalytic contact points are limited. Too high a proportion damages the overall capacity, and too low a proportion leads to insufficient catalysis of lithium carbonate in the three-dimensional space. The lithium replenishment materials lithium carbonate and magnesium silicate mineral materials have almost no electrical conductivity, and a carbon nanofiber network is required to provide electrical conductivity. Too high a proportion of carbon materials damages the lithium replenishment capacity, and too low a proportion of carbon materials damages the lithium replenishment effect.
[0186] Example 6 uses blocky carbon materials to replace carbon nanofibers, resulting in uneven distribution of the components of the composite lithium supplement material, decreased overall conductivity, and poor catalytic effect. The delithiation potential is higher than 4.2V, and only a small amount of lithium supplement effect can be exerted. Example 7 uses lithium oxalate to replace lithium carbonate, showing better lithium supplement effect and improved cycle life. Its theoretical lithium supplement capacity is 525mAh / g. The composite lithium supplement material has a good lithium supplement effect and a cycle life improvement of more than 75%; Example 8 does not form a composite lithium supplement material through liquid phase crystallization. Under this experimental condition, the particle size of lithium carbonate itself cannot be reduced, and the contact sites between the catalyst and lithium carbonate are extremely limited. At the same time, the conductivity is difficult to guarantee. Under the combined effect, the composite lithium supplement material has limited performance in soft-pack batteries because this method cannot guarantee the reduction of lithium carbonate particle size and the effective contact between the catalyst and lithium carbonate.
[0187] The solution provided in the embodiment of the present application is of great significance for optimizing the lithium replenishment technology using catalysts in lithium batteries and improving battery performance. By precisely controlling the composition and structure of the composite lithium replenishment material, long-term stability of battery capacity and significant improvement of cycle life can be achieved.
[0188] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A composite lithium supplement material, characterized in that: The invention comprises a matrix containing a magnesium silicate mineral material and a lithium supplement material loaded in the matrix; the magnesium silicate mineral material has pores which can accommodate the lithium supplement material.
2. The composite lithium supplement material according to claim 1, characterized in that: The substrate also contains a conductive material; And / or, the magnesium silicate mineral material contains magnesium oxide; and / or, the magnesium silicate mineral material is fibrous; And / or, the lithium supplement material includes at least one of lithium carbonate, lithium oxalate, and lithium squarate; And / or, in the composite lithium-supplementing material, the particle D50 of the loaded lithium-supplementing material is 50nm to 800nm.
3. The composite lithium supplement material according to claim 2, characterized in that: The magnesium silicate mineral material includes at least one of nano sepiolite, serpentine, brucite and hydromagnesite; And / or, the conductive material is conductive nanofibers, which are interwoven with the fibers in the magnesium silicate mineral material to form a three-dimensional network structure; And / or, the conductive material includes at least one of carbon nanofibers, carbon nanotube conductive fibers, graphene / carbon nanotube composite conductive nanofibers, and polyaniline conductive nanofibers; And / or, in the pores of the magnesium silicate mineral material, the magnesium oxide is arranged in contact with the lithium supplement material.
4. The composite lithium supplement material according to claim 3, characterized in that: In the magnesium silicate mineral material, the average fiber diameter is 100nm to 200nm, and the fiber length is 2μm to 10μm; And / or, in the conductive nanofibers, the average fiber diameter is 1 nm to 5 nm, and the fiber length is 1 μm to 20 μm; And / or, in the magnesium silicate mineral material, the mass percentage of magnesium oxide is 40% to 60%.
5. The composite lithium supplement material according to any one of claims 2 to 4, characterized in that: In the matrix, the mass ratio of the magnesium silicate mineral material to the conductive material is 1:(1-4); And / or, in the composite lithium-supplementing material, the mass percentage of the lithium-supplementing material is 70% to 80%; And / or, in the composite lithium supplement material, the mass percentage of the magnesium silicate mineral material is 4% to 15%; And / or, in the composite lithium supplement material, the mass percentage of the conductive material is 10% to 25%; And / or, in the composite lithium supplement material, the mass percentage of magnesium oxide is 2% to 7.5%.
6. A method for preparing a composite lithium supplement material, characterized in that: The following steps are involved: Preparing a substrate comprising a magnesium silicate mineral material; the magnesium silicate mineral material having pores therein; The lithium supplement material is loaded into the pores of the magnesium silicate mineral material to obtain a composite lithium supplement material.
7. The method for preparing the composite lithium supplement material according to claim 6, characterized in that: The matrix also contains a conductive material, and the preparation of the matrix includes the following steps: dissolving the magnesium silicate mineral material, the conductive material precursor, and the dispersant in water to form a hydrogel, and then freeze-drying the hydrogel to form an aerogel; sintering the aerogel under an inert atmosphere to obtain the matrix with a three-dimensional network structure; And / or, loading the lithium supplement material into the pores of the magnesium silicate mineral material comprises the steps of: immersing the substrate into a solution of the lithium supplement material, taking it out and immersing it in an anti-solvent for stripping and recrystallization, and drying to obtain the composite lithium supplement material loaded with the lithium supplement material; And / or, the lithium supplement material includes at least one recrystallizable lithium-rich material selected from lithium carbonate, lithium oxalate and lithium squarate; And / or, the magnesium silicate mineral material includes at least one of nano-sepiolite, serpentine, brucite, and hydromagnesite; And / or, the conductive material precursor includes at least one of bacterial cellulose, graphene oxide, polyacrylonitrile, and thermoplastic polyurethane.
8. The method for preparing the composite lithium supplement material according to claim 7, characterized in that: In the hydrogel, the mass ratio of the magnesium silicate mineral material to the conductive material precursor is 1:(2-20); And / or, in the hydrogel, the mass percentage of the dispersant is 0.3% to 0.8%; And / or, the dispersant includes at least one of polyvinylidene fluoride, polyvinyl pyrrolidone, polyethylene oxide, and polyvinyl alcohol; And / or, the temperature condition for preparing the hydrogel is 50° C. to 80° C.; And / or, the heating rate of the sintering treatment is 1°C / min to 5°C / min, the holding temperature is 600°C to 800°C, and the duration is 4h to 8h; And / or, the solution of the lithium supplementing material is a saturated solution; And / or, the anti-solvent comprises at least one of ethanol, acetone, and tetrahydrofuran; And / or, the recrystallization treatment step may be repeated multiple times; And / or, the temperature condition of the drying treatment is 200°C to 300°C.
9. A secondary battery, characterized in that: The secondary battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; wherein the positive electrode sheet contains the composite lithium supplement material as claimed in any one of claims 1 to 5 or the composite lithium supplement material prepared by the method as claimed in any one of claims 7 to 8.
10. The secondary battery according to claim 9, characterized in that In the positive electrode material layer of the positive electrode sheet, the mass percentage of the composite lithium supplement material is 1% to 3%; And / or, the positive electrode material system of the secondary battery is a lithium iron phosphate system, and as the secondary battery operates, the magnesium salt in the composite lithium supplement material is converted into magnesium carbonate.